Information strategy failure: personal interaction success, in urban residential food waste segregation. (15th October 2016) - Dai, Y.C.; Lin, Z.Y.; Li, C.J.; Xu, D.Y.; Huang, W.F.; Harder, M.K.
Abstract: Direct measurements were taken of residential food waste sorting in a sample from over 5000 communities (5 million households) assigned to a pilot program delivered by government branches in Shanghai which relied on an information strategy for implementation. The results are compared to a population of N = 36 similar communities (36, 000 households) assigned to a different program which involved considerable personal interaction. The results show that the information–based program communities did not noticeably sort their waste, whereas those given personal interaction approaches were very successful, with purity rates of 95%(8) and extra costs of about 50 RMB (8 USD) per household. This is a rare direct comparison of two different programs at such large scales, 6–36 months after launch, and suggests that personal interaction approaches should be considered by policy makers. Qualitative key informant interviews yielded data on each program's activities, which provide suggestions for further studies of the underlying behaviour change determinants involved. Highlights: A rare large scale study of two strategies for recycling behaviour change is reported. A large scale information strategy delivery for food waste sorting is shown to fail. A large scale personal interaction strategy for food waste sorting is very successful. Food waste separation purity rates of 95%(8); extra costs of 8 USD per household; 36000 h.